Does The Purchase Preference and Consumer Beliefs can Predicts Increased of Repurchase Intention of Traditional Culinary in Indonesia? - MJ Renwarin, Joseph; Sudiantini, Dian; Fahrani, Haifa; Maulydiawati, Maulydiawati; Jessica, Thentyana; Xaverius Jordi Hanzdima, Fransiskus; Tannady, Hendy (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
Kuningan Regency with an area of around 1,110 Km2 which 3.14% of the total area of West Java Province with a population of 1,087,105 people. In 2020 there was a significant increase compared to the previous year, reaching 600%. This increase can also be a great opportunity for MSMEs or creative industry players in Kuningan Regency, West Java, one of which is Ibu Misarah's sticky rice. Consumers of Ms. Misrah's sticky rice have spread to the Jakarta area, but consumers only buy tape at certain times. The sustainability of MSMEs is also an important goal in the development of the Kuningan Regency area. This study aims to explore the effect of purchase preference and consumer beliefs on repurchase intention by using an online questionnaire instrument with a total of 100 respondents. Data processing in this study used the partial least square structural equation modeling technique (SEM-PLS). The results of this study indicate that purchase preference and consumer beliefs affect repurchase intention.